Cariesprofilactic and parodontoprotective effects of oral gel “Quertulin” on rats, which received prednisolone - Valda, A. V.; Levitsky, A. P. (Journal of Education, Health and Sport, 2017)
Aim: To determine stomatoprotective effects of new complex phytogel “Quertulin” (quercetin + inulin + calcium citrate) on rats, which received prednisolone. Methods: The mucoso-adgesive oral gel “Quertulin” (quercetin + inulin + calcium citrate) was used. The prednisolone was introduced per os in dose of 10 m/kg (first 2 days) and 5 mg/kg (next 12 days). The gel “Quertulin” was applicated in dose 0,3 ml/rat everyday with first day during 14 days. The activities of elastase and contents of malonic dialdehide (MDA) and hyaluronic acid were determined into gum. The degree of dental caries and the degree of parodonte atrophia were determined. Results: It was established lowering of levels of lysozyme, catalase and hyaluronic acid, but increase levels of MDA, elastase, urease into gum of rats, which received prednisolone. The application of gel “Quertulin” normalized most of the indices. Conclusion: The oral applications of gel “Quertulin” has parodontoprotective and cariesprophylactic actions at prednisolone use.